2001
DOI: 10.1099/0022-1317-50-10-860
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cdtABC genes encoding cytolethal distending toxin among Haemophilus ducreyi and Actinobacillus actinomycetemcomitans strains

Abstract: The aim of this study was to investigate the presence of the three cdtABC genes responsible for production of cytolethal distending toxin (CDT) in Haemophilus ducreyi and Actinobacillus actinomycetemcomitans strains. Of 100 H. ducreyi strains from the culture collection of the University of Go Èteborg (CCUG), 27 strains with low or intermediate cytotoxic titre (<1 in 10 4 ) and 23 of the remaining isolates with a high cytotoxic titre (>1 in 10 4 ) were selected. Twenty-nine strains of H. ducreyi were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 11 publications
1
39
0
1
Order By: Relevance
“…Strains of Campylobacter species Haem. ducreyi, A. actinomycetemcomitans, E. coli, Shigella species and EHS that lack a full complement of CDT genes and/or activity have been described elsewhere (Abuoun et al, 2005;Ahmed et al, 2001;Asakura et al, 2007b;Dassanayake et al, 2005b;Fabris et al, 2002;Hyma et al, 2005;Janka et al, 2003;Johnson & Lior, 1987;Solnick & Schauer, 2001;Yamano et al, 2003). …”
Section: Cellular Entry Of Cdtbmentioning
confidence: 99%
“…Strains of Campylobacter species Haem. ducreyi, A. actinomycetemcomitans, E. coli, Shigella species and EHS that lack a full complement of CDT genes and/or activity have been described elsewhere (Abuoun et al, 2005;Ahmed et al, 2001;Asakura et al, 2007b;Dassanayake et al, 2005b;Fabris et al, 2002;Hyma et al, 2005;Janka et al, 2003;Johnson & Lior, 1987;Solnick & Schauer, 2001;Yamano et al, 2003). …”
Section: Cellular Entry Of Cdtbmentioning
confidence: 99%
“…CDT is prevalent in A. actinomycetemcomitans strains. Ahmed et al (2001) found that 43 of 50 strains from periodontitis patients contained all three cdt genes and expressed CDT activity. In another study, PCR of subgingival plaque samples revealed that 13 of 106 diseased sites in 146 patients with aggressive and chronic periodontitis contained A. actinomycetemcomitans expressing all three cdt genes (Tan et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…actinomycetemcomitans is the only oral bacterial species known to produce CDT (70). A number of studies collectively support that CDT may be important in the pathogenesis of aggressive periodontitis (1,19,64), although the actual contribution of CDT to this disease is not yet understood. In vitro studies have revealed that CDT stimulated receptor activator of NF-B ligand (RANKL) in human gingival fibroblasts (HGF) (9), which comprise the major cell population of the gingival connective tissue (5).…”
mentioning
confidence: 99%